A highly fire-retardant rigid polyurethane foam capable of fire-warning. (January 2022) - Ma, Zhewen; Zhang, Jianzhong; Liu, Lei; Zheng, Hua; Dai, Jinfeng; Tang, Long-Cheng; Song, Pingan
Abstract: Fabrication of flame-retardant coatings as a real-time fire-alarm sensor has been proved to be an effective method to improve the fire safety of polymeric foams. Herein, we reported a three-layer "sandwich-like" fire-retardant coating for rigid polyurethane (PU) foam by using phytic acid (PA), flame retardant copolymer (PVH), graphene oxide (GO), carbon nanotubes (CNTs), and boron nitride (BN) as building blocks. The resultant PU foam demonstrates a rapid fire-alarm response of ∼8 s and displays a continuing fire warning at high temperatures even exposed to flame. In addition, this foam exhibits a self-extinguishing behavior with a high limited oxygen index of 58.0 vol%. Meanwhile, the peak heat release rate, total smoke release, and peak CO production rate are decreased by 49%, 41%, and 67% respectively. This work provides an innovative strategy for creating fire-retardant foam materials that can detect fire hazards, holding great promise for extensive applications in industries, such as construction and transportation areas. Graphical abstract: Image 1 Highlights: A sandwich-like fire-retardant coating is developed to improve fire-retardancy of PU foam. The coated PU shows an exceptional flame retardance at a coating thickness of 200 μm. The coated PU shows a fire-warning response time (∼8 s) and a long working time in the flame.